Motivating Students to Perform Better Orally in a Communicative Language Teaching Framework - CHELBI, Rym Ghosn El-Bel (Journal of Human Sciences, 2011)
“Communicative Language Teaching” is a method used to motivate the students to better oral performance. In this article, we have presented the characteristics of this method that we have tested through a study realized in the department of Foreign Language at Mentouri University Constantine. The results that we have obtained after the signing of two questionnaires, one addressed to a sample of teachers and another to a sample of second year L.M.D. students of English, demonstrated that the method is motivating and helps students for a better oral performance.